Standard reference and percentiles of maximum respiratory pressures values of healthy children aged 7–10 years Distribuição padrão e percentuais dos valores de pressão respiratória máxima de crianças saudáveis de 7 a 10 anos de idade - Parazzi P.L.F. (2022)
© 2022 Sao Paulo Pediatric Society. All rights reserved.Objective: This study aims to present standard reference for values of maximum respiratory pressures of healthy schoolchildren, according to gender. Methods: This is a cross-sectional study involving healthy children aged 7–10 years. Data of body mass and height were evaluated to calculate body mass index (BMI). In addition, forced expiratory volume in 1 second (FEV1) and maximal expiratory pressure values were evaluated according to the American Thoracic Society. The maximal inspiratory pressure (MIP) and data of maximal expiratory pressure (MEP) obtained in the study showed normal distribution and curves were built by the Lambda–Mu–Sigma (LMS) method, as well as the values of MIP and MEP percentiles 3, 10, 25, 50, 75, 90, and 97 for each gender. Results: MIP and MEP data were collected from 399 schoolchildren. All schoolchildren in the sample had adequate FEV1 and BMI. The study showed an increase in respiratory pressure values with age progression. The MIP and MEP values of girls were of 53.4±11.0 and 61.8±12.5cmH2O, respectively, and those of boys were 59.9±13.6 and 69.6±15.7cmH2O, respectively. Conclusions: Normal curves and percentiles were developed for MIP and MEP values of healthy schoolchildren. The extreme percentiles (3rd and 97th) were determined, and a specific graph was elaborated for each group. These graphs may help clinical follow-up and therapeutic monitoring of different pediatric populations.